A follow - up to 'Good night!... again."

Algebra Level 4

( 6 2 a + 3 b ) ( 6 2 a + 3 c ) ( a b ) ( a c ) + ( 6 2 b + 3 c ) ( 6 2 b + 3 a ) ( b c ) ( b a ) + ( 6 2 c + 3 a ) ( 6 2 c + 3 b ) ( c a ) ( c b ) \dfrac{(6 - 2a + 3b)(6 - 2a + 3c)}{(a - b)(a - c)} + \dfrac{(6 - 2b + 3c)(6 - 2b + 3a)}{(b - c)(b - a)} + \dfrac{(6 - 2c + 3a)(6 - 2c + 3b)}{(c - a)(c - b)}

Calculate the value of the expression above for distinct real values of a a , b b , and c c .


The answer is 19.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Jun 24, 2018

X = cyc ( 6 2 a + 3 b ) ( 6 2 a + 3 c ) ( a b ) ( a c ) Let x = a + 6 , y = b + 6 , z = c + 6 = cyc ( 3 y 2 x ) ( 3 z 2 x ) ( x y ) ( x z ) = cyc ( 9 y z 6 x y 6 z x + 4 x 2 ) ( z y ) ( x y ) ( y z ) ( z x ) = cyc 9 ( y z 2 y 2 z ) + 6 ( x y 2 z 2 x ) + 4 ( z x 2 x 2 y ) x y 2 x 2 y + y z 2 y 2 z + z x 2 z 2 x = 19 × x y 2 x 2 y + y z 2 y 2 z + z x 2 z 2 x x y 2 x 2 y + y z 2 y 2 z + z x 2 z 2 x = 19 \begin{aligned} X & = \sum_{\text{cyc}}\frac {(6-2a+3b)(6-2a+3c)}{(a-b)(a-c)} & \small \color{#3D99F6} \text{Let }x = a+6, y = b+6, z=c+6 \\ & = \sum_{\text{cyc}}\frac {(3y-2x)(3z-2x)}{(x-y)(x-z)} \\ & = \sum_{\text{cyc}}\frac {(9yz-6xy-6zx+4x^2)\color{#3D99F6}(z-y)}{(x-y)\color{#3D99F6}(y-z)(z-x)} \\ & = \sum_{\text{cyc}}\frac {9(yz^2-y^2z)+6(xy^2-z^2x)+4(zx^2-x^2y)}{xy^2-x^2y+yz^2-y^2z+zx^2-z^2x} \\ & = 19 \times \frac {xy^2-x^2y+yz^2-y^2z+zx^2-z^2x}{xy^2-x^2y+yz^2-y^2z+zx^2-z^2x} \\ & = \boxed{19} \end{aligned}

Well done!

Rudrayan Kundu - 2 years, 11 months ago

Log in to reply

Thanks. Glad that you like it.

Chew-Seong Cheong - 2 years, 11 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...